CONTACTLESS WAYS AND MEANS OF COMBINED PROFILOMETRY . - A. P. Markov; V. F. Gogolinsky; A. A. Azarko; A. G. Starovojtov; E. M. Patuk (Литьë и металлургия)
The modern ways and technologies of combined profilometry of extended surfaces on the basis of pneumatic-optical and optical-electronic structures of informational transformations are examined.